Non-equilibrium modeling on the plasma–electrode interaction in an argon DC plasma torch. (25th August 2021) - Sun, Jiang-Hong; Sun, Su-Rong; Niu, Chong; Wang, Hai-Xing
Abstract: A 2D two-temperature chemical non-equilibrium model considering both cathode and anode space-charge sheath is applied to investigate the plasma–electrode interaction in a laminar argon DC plasma torch working at atmospheric pressure. In order to validate the model, the predicted arc voltage is compared with experimental values under different working conditions, and a reasonable agreement is obtained. The distributions of arc characteristics in the plasma column and electrode regions of a DC arc plasma torch are analyzed in detail. Moreover, the effects of thoriated tungsten, pure tungsten and non-uniform thoriated tungsten cathodes on the plasma characteristics inside the DC plasma torch are investigated. It is found that a constricted arc attachment with the highest current density is obtained at the non-uniform cathode, leading to the largest velocity and electric potential drop in the plasma column. The pure tungsten cathode produces the highest temperatures and heat flux along the cathode surface, which is caused by the largest arc voltage and intense space-charge sheath heating. The temperature and heat flux density on the thoriated tungsten cathode are the lowest, leading to a diffuse distribution of current density. The results indicate that the different cathodes can exert an important influence upon the plasma behavior near the cathode. Furthermore, the torch exit parameters are also slightly different due to their different arc voltages and overall input power.